Baf45a Mediated Chromatin Remodeling Promotes Transcriptional Activation for Osteogenesis and Odontogenesis - Busby, Theodore; Chen, Yuechuan; Godfrey, Tanner C.; Rehan, Mohammad; Wildman, Benjamin J.; Smith, Caris M.; Hassan, Quamarul (Frontiers in Endocrinology, 2022)
Chromatin remodeling, specifically the tissue-specific regulation in mineralized tissues, is an understudied avenue of gene regulation. Here we show that Baf45a and Baf45d, two Baf45 homologs belong to ATPase-dependent SWI/SNF chromatin remodeling complex, preferentially expressed in osteoblasts and odontoblasts compared to Baf45b and Baf45c. Recently, biochemical studies revealed that Baf45a associates with Polybromo-associated BAF (PBAF) complex. However, the Baf45d subunit belongs to the polymorphic BRG1-associated factor (BAF) complex. Protein profiles of osteoblast and odontoblast differentiation uncovered a significant increase of BAF45A and PBAF subunits during early osteoblast and odontoblast maturation. Chromatin immunoprecipitation sequencing (ChIP-seq) during the bone marrow stromal cells (BMSCs) differentiation showed higher histone H3K9 and H3K27 acetylation modifications in the promoter of Baf45a and Baf45d and increased binding of bone and tooth specific transcription factor RUNX2. Overexpression of Baf45a in osteoblasts activates genes essential for the progression of osteoblast maturation and mineralization. Furthermore, shRNA-mediated deletion of Baf45a in odontoblasts leads to markedly altered genes responsible for the proliferation, apoptosis, DNA repair, and modest decrease in dentinogenic marker gene expression. Assay for Transposase-Accessible Chromatin sequencing (ATAC-seq) assay in Baf45a knockout osteoblasts revealed a noticeable reduction in chromatin accessibility of osteoblast and odontoblast specific genes, along with transcription factor Atf4 and Klf4. Craniofacial mesenchyme-specific loss of Baf45a modestly reduced the mineralization of the tooth and mandibular bone. These findings indicated that BAF45A-dependent mineralized tissue-specific chromatin remodeling through PBAF-RUNX2 crosstalk results in transcriptional activation is critical for early differentiation and matrix maturation of mineralized tissues.